IS YOUR STRATEGIC PLAN A MEANS OR AN END? Four principles that will help improve your strategic planning process. - WANG, KEL (Public Management (00333611), 2021)
The article discusses, how long does it take to develop, and start implementing a strategic plan, with example, topics including, Conversations and Learning over Process, Community Collaboration over a Siloed Approach, Responding to Change over Sticking to the Plan, and A Working Strategy over a Complex Framework and Thick Documentation.